2009
DOI: 10.1111/j.1360-0443.2008.02437.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, placebo‐controlled trial of modafinil (200 mg/day) for methamphetamine dependence

Abstract: Modafinil demonstrated promise in reducing methamphetamine use in selected methamphetamine-dependent patients. The study findings support definitive trials of modafinil in larger multi-site trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 43 publications
3
113
0
Order By: Relevance
“…Camacho and Stein (2002) first reported that ( ± )-MOD was effective in treatment of amphetamine dependence in a patient with comorbid social phobia. This finding was later supported by a number of studies demonstrating that ( ± )-MOD was effective in reducing cocaine and methamphetamine use, subjective euphoric effects, craving, and withdrawal symptoms (Dackis et al, 2005;Dackis et al, 2003;Goudriaan et al, 2013;Hart et al, 2008;Malcolm et al, 2006;McGregor et al, 2008;Shearer et al, 2009). In experimental animals, ( ± )-MOD has been reported to block reinstatement of drug-seeking caused by cocaine, heroin, methamphetamine, or drug-associated environmental cues (Mahler et al, 2014;Reichel and See, 2010;Tahsili-Fahadan et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…Camacho and Stein (2002) first reported that ( ± )-MOD was effective in treatment of amphetamine dependence in a patient with comorbid social phobia. This finding was later supported by a number of studies demonstrating that ( ± )-MOD was effective in reducing cocaine and methamphetamine use, subjective euphoric effects, craving, and withdrawal symptoms (Dackis et al, 2005;Dackis et al, 2003;Goudriaan et al, 2013;Hart et al, 2008;Malcolm et al, 2006;McGregor et al, 2008;Shearer et al, 2009). In experimental animals, ( ± )-MOD has been reported to block reinstatement of drug-seeking caused by cocaine, heroin, methamphetamine, or drug-associated environmental cues (Mahler et al, 2014;Reichel and See, 2010;Tahsili-Fahadan et al, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…It has been shown to improve cognitive performance in healthy research volunteers (Randall et al, 2005;Repantis et al, 2010;Turner et al, 2003), with a larger effect in patients with neuropsychiatric disorders such as attention-deficit hyperactivity disorder and schizophrenia (Turner et al, 2004a, b). Cognition-enhancing agents have been suggested as potential treatment medications for stimulant addiction (Sofuoglu, 2010), and some success with such agents has been observed in the treatment of cocaine (Dackis et al, 2005) and MA dependence (Shearer et al, 2009), but few studies have examined the direct effects of these potential pharmacotherapies on behavioral and neural measures of cognition in stimulant-abusing subjects. Modafinil appears to be safe and well-tolerated by MAdependent subjects McGaugh et al, 2009), and some evidence suggests that it enhances the retention of MA-dependent subjects in programs that involve contingency management and cognitive behavioral therapy (Heinzerling et al, 2010), but little is known about the effects of modafinil on cognitive function in MA-dependent individuals (see Kalechstein et al (2010) for an example of working-memory enhancement in this sample).…”
Section: Introductionmentioning
confidence: 99%
“…None showed clear efficacy for this indication. However, two of these studies (Shearer et al, 2009;Anderson et al, 2012) indicate through post hoc analyses that patients compliant with the medication do achieve better abstinence than noncompliant patients. Another study (Heinzerling et al, 2010) showed trends toward increased efficacy among users with high baseline methamphetamine use and low attendance in cognitive-behavioral therapy (although neither was statistically significant).…”
mentioning
confidence: 99%